Hair and Scalp Disorders - Kutlubay, Zekayi; Serdaroglu, Server (IntechOpen, 2017)
This textbook contains the latest advances and scientific knowledge from the leading experts in hair biology, hair disorders, and clinical trichology. The book consists of ten sections in which hair biology, hair genetics, hair diagnostics, hair loss types, pathogenesis, treatment options, and restoration techniques are discussed. This book also emphasizes on various genetic and nongenetic alopecia types, differential diagnosis, and the measurement of hair loss. One chapter of the book is devoted to natural products for hair care and treatment. We believe that this textbook will serve as a comprehensive guide to many physicians dealing with hair disorders in their clinical practice.